The outcome of breast cancer based on the expression of c-erbb2 , estrogen receptor and progesterone receptor: kelantan experience 2002-2004 - Mohamed, Moharzudi (2010)
Breast cancer in the most common cancer among Malaysian women. There are many prognostic factors contributing to the disease and the outcome of the patients. Hence, a retrospective study was carried out aiming to observe the outcome of breast cancer patient in terms of overall survival with relation to estrogen receptor (ER), progesterone receptor (PR) and c erbB-2 expression. In addition, patient's age, histological subtype, tumor grade, tumor size and lymph node involvement were also analyzed against overall survival, ER, PR and c erbB-2 expression. 115 cases of breast cancer diagnosed in three years, 2002 to 2004, were reviewed. It was found that ER and PR status were positive in 45.2% and 48.7% respectively while 39.1% showed c erbB-2 overexpression. There was significant association between ER status with tumour grade, tumour size, and PR status. Significant association was also found between PR status with tumour grade. There was significant association between c erbB-2 status with tumour grade and lymph nodes involvement. Univariate analysis showed shorter overall survival in patients with lymph node positive status, ER negativity, and c-erbB-2 oncoprotein overexpression. In multivariate prognostic analysis, c erbB-2 status was the strongest independent prognostic factor and ER status was the second most significant independent prognostic factor for overall survival. However, lymph node status was not a significant independent prognostic factor. From these finding, it was concluded that c erbB-2 and ER status was the strongest prognostic factors contributing to the outcome of breast cancer patients.